Co-management in a Landscape of Resistance: The Political Ecology of Wildlife Management in Western Alaska - Spaeder, Joseph J. (Anthropologica, 2022)
This paper examines the evolution, structure and operation of co-management regimes for caribou and brown bear from a political ecology perspective. Since 1989, Yup’ik Eskimo hunters and government managers in Western Alaska have established a set of regimes for the joint management of caribou and brown bear. The creation of these decentralized management institutions occurs in the face of divergent perceptions of wildlife population dynamics, incongruent land tenure systems and long-standing traditions of local resistance to external game regulation. Political ecology serves as a conceptual framework for developing an integrated understanding of how environmental factors, political forces and cultural traditions interact to produce social conflict and, in these cases, generate new institutional responses to conflict.